The Use of Interactive Mobile Technology to Improve Learning Outcomes: A Systematic Review - Mudasir, Mudasir (Journal Mobile Technologies (JMS), 2024)
This study systematically reviews the impact of interactive mobile technologies on students’ learning outcomes in Indonesia. By analyzing 24 studies published between 2019 and 2024, the research highlights the effectiveness of mobile applications, augmented reality (AR), and gamified learning platforms in enhancing conceptual understanding, motivation, and engagement. Mobile applications were most commonly implemented due to accessibility and adaptability, while AR and gamification contributed to improved focus and comprehension through immersive visualization and challenge-based activities. Despite these benefits, successful integration depends on instructional design quality, teacher digital literacy, and institutional support. Short-term interventions dominate the current literature, leaving gaps in understanding long-term sustainability. The study recommends expanding research to non-STEM subjects, integrating adaptive and AI-based systems, and employing mixed-method approaches to provide comprehensive insights into effective technology-enhanced learning.